Gestational Weight Gain and Peripartum Cardiomyopathy in a Twin Pregnancy - Hiroko Matsumiya; Naotaka Saito; Hisanori Minakami; Soromon Kataoka (Hindawi Limited, 2015)
Preeclamptic twin pregnancy with larger gestational weight gain (GWG) is suggested to have a higher risk of peripartum cardiomyopathy (PPCM). This was true in a 5-year experience at a single center. A primiparous woman with twins and prepregnancy weight of 51.0 kg exhibited hypertension at gestational week (GW) 32−6/7 and GWG of 18.3 kg (6.0 kg and 2.9 kg during the last four weeks and one week of gestation, resp.) concomitant with generalized edema, gave birth at GW 34−4/7, developed proteinuria, cough, and dyspnea postpartum, and was diagnosed with preeclampsia and PPCM showing left ventricular ejection fraction of 34% and plasma BNP level of 1530 pg/mL. This was the only case of PPCM among 101 (12 with preeclampsia) and 3266 women with twin and singleton pregnancies, respectively. Thus, PPCM occurred significantly more often in women with preeclamptic twin pregnancies than in women with singleton pregnancies (8.3% [1/12] versus 0.0% [0/3266], P=0.0355). This patient showed the greatest weight gain of 6.0 kg during the last four weeks of gestation and the greatest weight loss of 19.2 kg during one month postpartum among 90 women with twin deliveries at GW ≥ 32.